BIODIVERSITAS IKAN DI PERAIRAN DUSUN MELIAU KABUPATEN KAPUAS HULU - Soetignya, Widadi Padmarsari (Akuatik Tropis (Akuatrop): Journal of Tropical Aquatic Resource Management (ISSN:3063-7414), 2023)
This study aimed to assess the fish biodiversity in the waters of Meliau Village Kapuas Hulu Regency. Fish samples were collected during three periods: July and October 2013 and February 2015. The study area was divided into four sampling stations: Leboyan River, Balai Aram Lake, Lukuk Lake and Merebung Lake. In this study, 56 fish species were identified, they represent 35 genera and 20 families. Diversity index in the wet season was greater than the other seasons. The fish diversity of Leboyan river was the greater than the fish diversity of Balai Aram Lake. This study showed that the lakes (Balai Aram, Merebung and Lukuk) are considered to be important habitat for some target fish species like Leptobarbus menalopterus, Channa pleurophthalmus, C. mauriolides and C. micropeltes for their role in spawning and nursery ground. The value of Dissolved Oxygen and pH were environment factors which were not suitable for fish, while diversity index of plankton was classified as low-medium (1.0-2.16).